Administrators perception on challenges in implementing disciplinary action in public sector / Firdaus M. Ilham - M. Ilham, Firdaus (2010)
Discipline act as a guidance on how people should behave and react in order to live a life with control. It helps every person to take responsibility for their behavior. Every school, institution and organization has their own disciplinary rules to act as a guidance or material for controlling behavior of the people within that organization. Thus discipline is very important in order for an organization to run efficiently and smoothly. However, in every organization, there were several employees that have disciplinary problem such as sexual harassment, absenteeism, punctuality issues, and fighting with colleagues. Such problems can jeopardize organizations whereby it may give negative impact to the organization such as fall in productivity. Consequently, disciplinary action needs to be done in order to set a good example to other person that wrongful act will eventually faced consequences. However, when talk about disciplinary action, there are several question arise, such as, how effective the disciplinary action in resolving the problem? What are the obstacles that administrator faced in conducting it? It is commonly known that administrator who involve in disciplinary action procedure may face problems and challenges while conducting it. Therefore, in this study, there are four independent variables that been identified which become the main challenges for the administrator in conducting disciplinary procedures and which among the factors that affect the implementation of disciplinary action procedure.